(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2013)
Comparison of spent labor resources and effectiveness estimation of the same geodetic network creation by using conventional and satellite technology are presented in the article. All of the necessary works were carried out on the same territory in Geodynamic Testing Ground near Yerevan. As a result, the creation of geodetic network by satellite technology is 3.59 times as effective as conventional triangulation method. Besides the abilities of satellite technology and the positive properties are enumerated in contrast with conventional methods.